Use of Virtual Reality to Improve the Quality of the Hospital Stay for Patients in Neurosurgery - Vayssiere, Pia; Constanthin, Paul E.; Baticam, Nalla Silva; Herbelin, Bruno; Degremont, Christine; Blanke, Olaf; Schaller, Karl; Bijlenga, Philippe (Frontiers in Virtual Reality, 2021)
Background: Virtual Reality (VR) technologies have numerous beneficial applications for patients during hospitalization (through complete immersion in a virtual, distant place allowing to “escape” from the context of hospitalization). Their positive effects in pain and anxiety management, neurorehabilitation and psychotherapy have been demonstrated. Here, we evaluated the effects of VR on the quality of hospitalization and postoperative pain after neurosurgery. Methods: Patients hospitalized in our department between 2019 and 2020 were prospectively enrolled and divided into a group that received a personal, 30-minutes-long, VR session using an Oculus Go ™ VR headset (VR group) or not (non-VR group). Surgeries were classified in simple or complex spinal and simple or complex cranial. Patients’ overall satisfaction was considered as primary outcome, with secondary outcomes encompassing duration of hospitalization, pain reduction and patients’ opinion regarding VR. Results: 161 patients were enrolled (77 in the VR group and 84 in the non-VR group). There was no statistical difference between the two groups regarding satisfaction. The VR group presented with a significantly longer duration of hospitalization and higher maximal pain. Interestingly, pain reduction during hospitalization was significantly higher in the VR group, particularly in simple surgeries and spine surgeries. A vast majority of the VR group patients appreciated their VR experience (89.2%) and advocated for its systematic use (83.8%). Conclusions: VR can improve pain reduction during hospitalization after neurosurgery, particularly for simple spine surgeries. Furthermore, patients experiencing VR appear to appreciate it and advocate for its systematic use in neurosurgery. Further research is warranted to identify patients for whom addition of VR during hospitalisation might bring the most benefit.